1995
DOI: 10.1111/j.1365-2958.1995.mmi_17030427.x
|View full text |Cite
|
Sign up to set email alerts
|

Maturation pathway of nisin and other lantibiotics: post‐translationally modified antimicrobial peptides exported by Gram‐positive bacteria

Abstract: SummaryLantibiotics form a family of highly modified peptides which are secreted by several Gram-positive bacteria. They exhibit antimicrobial activity, mainly against other Gram-positive bacteria, by forming pores in the cellular membrane. These antimicrobial peptides are ribosomally synthesized and contain leader peptides which do not show the characteristics of signal sequences. Several amino acid residues of the precursor lantibiotic are enzymatically modified, whereafter secretion and processing of the le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
123
0
1

Year Published

1996
1996
2011
2011

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 174 publications
(125 citation statements)
references
References 34 publications
1
123
0
1
Order By: Relevance
“…6) The type-A group is further divided into two subgroups, type-A(I) and type-A(II), based on the sizes, charges, and sequences of the leader peptides. 7) The biosynthetic pathway for the lantibiotics is as follows: [4][5][6][7] First, the lantibiotic prepeptide LanA, which consists of an N-terminal leader peptide followed by a C-terminal propeptide, is ribosomally synthesized. In the biosynthesis of type-A(I) lantibiotics, LanB and LanC are required for the dehydration of serines and threonines and the coupling of cysteines to dehydroresidues (cyclization) respectively.…”
mentioning
confidence: 99%
“…6) The type-A group is further divided into two subgroups, type-A(I) and type-A(II), based on the sizes, charges, and sequences of the leader peptides. 7) The biosynthetic pathway for the lantibiotics is as follows: [4][5][6][7] First, the lantibiotic prepeptide LanA, which consists of an N-terminal leader peptide followed by a C-terminal propeptide, is ribosomally synthesized. In the biosynthesis of type-A(I) lantibiotics, LanB and LanC are required for the dehydration of serines and threonines and the coupling of cysteines to dehydroresidues (cyclization) respectively.…”
mentioning
confidence: 99%
“…Apparently, nisin or one of its precursors is required for transcription of its own gene. In a follow-up study (Kuipers et al, 1995), this phenomenon was further analyzed. Northern blotting using mRNA from the AnisA strain revealed that, indeed, AnisA transcription was restored upon addition of nisin to the culture medium.…”
Section: Nisin Productionmentioning
confidence: 99%
“…These proteins belong to the class of two-component regulatory systems in which, in this case, NisR is the response regulator and NisK the signal sensor or sensor histidine kinase (for excellent reviews, see Schnell et al, 1988;Jung 1991;Sahl et al, 1995;de Vos et al, 1995). Three promoters, upstream of nisA, nisR and nisF, have been mapped by primer extension (Kuipers et al, 1993;Kuipers et al, 1995;de Ruyter et al, 1996;P. Saris, pers.…”
Section: Nisin Productionmentioning
confidence: 99%
“…It appears that Gram-positive bacteria prefer peptide signals, also termed peptide pheromones (5). These peptides are processed during secretion but may also be subject to complex post-translational modi cations such as nisin in lactococci (6) or peptide thiolactones in staphylococci (7). Although there are, as yet, no chemically characterized examples of quorum sensing signal molecules common to both Gram-negative and Gram-positive bacteria, a gene termed luxS has been identi ed which has homologues in both types of bacteria (8).…”
Section: Introductionmentioning
confidence: 99%